Access to Health Information - Gaudinat, A.; Managing Editor for the IMIA Yearbook Section on Access to Health Information (Yearbook of Medical Informatics, 2008)
Objectives To summarize current excellent research in the field of access to health information.Method Synopsis of the articles selected for the IMIA Yearbook 2008.Result Four articles from in,ternational peer reviewed journals were selected for this section. This selection is composed of two studies which gives an overview of how people currently access health information and two descriptions of original systems which show actual challenges and alternatives to better access information in the health domain.Conclusion The possibilities of access are increasingly more important for online health information, taking into mind the pros of the goal of universality and the cons of overabundance and unevenness of quality. Current research is going in the direction of studying the user behavior and building better alternative systems to reach health information. However more research should be done about the Web 2.0 technologies related to the access to Health information, since they are currently changing information access and selection paradigm.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; search engine